Method for preparing 2, 5-furandicarboxylic acid through selective catalytic oxidation of 5-hydroxymethylfurfural by using nano-microstructured multi-metal oxide
By using subcritical technology to prepare nano-structured polymetal oxide catalysts during biomass conversion, the problems of low conversion efficiency and poor selectivity in the prior art are solved, and efficient catalytic conversion of 5-hydroxymethylfurfural to 2 are achieved. ,The effect of 5-furandicarboxylic acid.
Patent Information
- Application Number
- CN202510060930.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2045-01-15
AI Technical Summary
The prior art has problems such as low conversion efficiency, poor selectivity, and harsh conditions in the process of converting biomass into high-value compounds, making it difficult to develop efficient, stable and low-cost catalysts.
By adjusting the temperature and pressure during the reaction process, subcritical technology is used to prepare nano-microstructured polymetal oxide catalysts, regulating their micromorphology and size, stimulating polymetal active sites, and improving catalytic activity.
Highly efficient catalytic conversion of 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid was achieved, which significantly improved yields and provided a new method for non-precious metal catalysts for industrial production.
Smart Images

Figure CN119455977A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biomass resource utilization and multi-metal oxide preparation, and specifically relates to a method for using nano-microstructured multi-metal oxides for selective catalytic oxidation of 5-hydroxymethylfurfural to prepare 2,5-furandicarboxylic acid. Background Art
[0002] Biomass is a renewable organic resource with abundant reserves, wide distribution and easy access. It has the advantages of being renewable and biodegradable, and is an ideal energy substitute. 5-Hydroxymethylfurfural, as an important bio-based platform compound, has received widespread attention due to its unique chemical structure and versatility. 5-Hydroxymethylfurfural can be converted into 2,5-furandicarboxylic acid through a series of catalytic reactions. The latter is a key high-value precursor that can be used to synthesize a variety of fine chemicals. The most noteworthy thing is that 2,5-furandicarboxylic acid has a conjugated rigid ring and dicarboxylic acid structure similar to terephthalic acid. It is an excellent precursor for synthetic polymers and can be used as an alternative material to terephthalic acid. With its renewability and easy degradation, it can alleviate the plastic pollution situation. However, the conversion of biomass to high-value compounds generally has problems such as low conversion efficiency, poor selectivity, and harsh conditions. Therefore, the development of efficient, stable and low-cost catalysts has become an important issue that needs to be solved urgently.
[0003] Subcritical fluids have unique advantages in the field of nanomaterial preparation due to their excellent solubility and mass transfer properties. The preparation of catalysts using subcritical technology has the advantages of high dispersibility, strong controllability, and rapid crystallization. Metal ions can quickly form smaller nanoparticles in subcritical fluids. By changing some conditions in the subcritical preparation of catalysts, the microscopic morphology and size of multi-metal oxides can be precisely controlled, thereby stimulating the active sites of multi-metal oxides and affecting the activity of the catalyst.
[0004] At present, precious metal materials have shown excellent catalytic performance in the process of catalyzing the conversion of 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid, but due to their high cost and difficulty in recycling, researchers prefer to find low-cost transition metal catalysts to replace precious metals. Studies have shown that multi-metal oxides have heterogeneous catalytic effects in electrocatalysis, photocatalysis and thermal catalysis. Multi-metal oxides are usually composed of two or more metal oxides. Due to the synergistic effect of multiple metals, they have rich active sites and show properties superior to single metal oxides. Therefore, designing a controllable and efficient catalyst preparation method to activate multi-metal active sites and synthesize highly active catalysts to efficiently catalyze the conversion of 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid has become a major challenge at present. Summary of the invention
[0005] In view of the above situation, the purpose of the present invention is to provide a method for selectively catalyzing the oxidation of 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid using a nanostructured multi-metal oxide. The nanostructure of the multi-metal oxide is regulated by adjusting the temperature and pressure during the reaction. The obtained multi-metal oxide has the characteristics of small size, multiple active sites and high catalytic activity, which provides a new method for developing a non-precious metal catalyst to catalyze the oxidation conversion of 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid.
[0006] The technical solution adopted in the present invention is as follows: A subcritical preparation method for a multi-metal oxide with adjustable nano-microstructure comprises the following steps: Step 1: dissolving a metal salt in an aqueous solvent, uniformly dispersing the mixture by ultrasonication, dripping an alkaline additive solution into the mixture under stirring, and fully stirring and mixing the mixture to obtain a uniform mixed solution; wherein the metal salt is a chloride, nitrate, acetate or sulfate corresponding to two or more metal elements selected from magnesium, aluminum, iron, cobalt, manganese, nickel, copper, zinc, gallium and indium; Step 2: The mixed solution obtained in step 1 is transferred into a temperature- and pressure-controlled reactor, and the temperature and pressure of the reactor are adjusted to make the liquid in the reactor reach a subcritical state, and react to rapidly form nanoparticles; Step 3: centrifugally separating the mixed suspension prepared in step 2, and sequentially washing, drying, and grinding to obtain a multi-metal oxide precursor; Step 4: placing the multi-metal oxide precursor prepared in step 3 in a muffle furnace for calcining to obtain the multi-metal oxide; The reaction temperature of step 2 is 150-200°C, and the reaction pressure is 0.4-5 MPa.
[0007] Furthermore, the metal salt in step 1 is a salt of two metals, the first metal is Mn, the second metal is Co, Cu or Ni, and the molar ratio of the first metal to the second metal is 1.5-3:1, preferably 2-2.5:1.
[0008] Furthermore, the metal salt in step 1 is a salt of two metals, the first metal is Co, the second metal is Cu or Cu and Zn, the molar ratio of the first metal to the second metal is 1.5-3:1, preferably 2-2.5:1; when the second metal is Cu and Zn, the molar ratio of the two is 1.5-3:1, preferably 2-2.5:1.
[0009] Furthermore, in step 1, the alkaline additive is at least one of sodium hydroxide, potassium hydroxide, aqueous ammonia, sodium carbonate, and potassium carbonate, and the alkaline additive solution is dripped into the metal salt solution to adjust the pH to 9-12.
[0010] Furthermore, in step 2, the reaction temperature is 170-180°C, and pressurized nitrogen is introduced into the reactor to make the reaction pressure in the reactor higher than the autogenous pressure of water in the reactor, and the reaction pressure is adjusted to 1.5-2 MPa.
[0011] Furthermore, the calcination temperature in step 4 is 300-400°C.
[0012] The present invention provides a multi-metal oxide with adjustable nano-microstructure, which can be well used in catalyzing the reaction of 5-hydroxymethylfurfural to prepare 2,5-furandicarboxylic acid. The application method is as follows: adding the multi-metal oxide, an alkaline additive and a 5-hydroxymethylfurfural solution into a microreactor with controllable temperature and pressure, sealing the microreactor, and catalyzing the oxidation of 5-hydroxymethylfurfural to generate 2,5-furandicarboxylic acid under the conditions of a temperature of 100-150°C, an oxygen pressure of 0.5-4 MPa and continuous magnetic stirring; after the reaction is completed, centrifuging and recovering the multi-metal oxide material.
[0013] Furthermore, the concentration of the 5-hydroxymethylfurfural solution is 10-100 mM, the mass ratio of the multi-metal oxide to 5-hydroxymethylfurfural is 1.2-2:1; the alkaline additive is sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate or calcium hydroxide, and the molar ratio of the alkaline additive to 5-hydroxymethylfurfural is 1 ~ 4:1.
[0014] The beneficial effects achieved by the present invention are: 1) The present invention utilizes the characteristics of high diffusion coefficient, high reaction rate and low surface tension of the solvent in the subcritical state, and achieves effective regulation of the nanostructure of the multi-metal oxide by adjusting the temperature and pressure during the reaction process, so that the formed multi-metal oxide has abundant active sites.
[0015] 2) The multi-metal oxide material prepared by the present invention can be used for the oxidation reaction of 5-hydroxymethylfurfural. By exerting its multi-metal synergistic effect, the multi-metal active sites are stimulated, the interfacial reaction between 5-hydroxymethylfurfural and the catalyst material is significantly promoted, and the yield of 2,5-furandicarboxylic acid production is improved.
[0016] 3) The present invention can provide a new method for replacing precious metal catalysts and developing new non-precious metal functional materials for the 2,5-furandicarboxylic acid industry. The multi-metal oxide material prepared by the present invention can be used in the oxidation reaction of 5-hydroxymethylfurfural, play a catalytic role, and improve the product conversion rate. The non-precious metal Mn, Co, and Cu-based multi-metal oxide materials have excellent catalytic effects, providing a new possibility for the industrial production of 2,5-furandicarboxylic acid using non-precious metal catalysts. In addition, in order to reduce the cost of precious metal use, reduce environmental pollution, and develop non-precious metal catalysts to promote the long-term development of the 5-hydroxymethylfurfural oxidation industry, a new method is provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 CoMn prepared in Example 1 of the present invention 2 O 4 XRD patterns of the samples.
[0018] Figure 2 The CoMn prepared in Example 1 of the present invention 2 O 4 SEM image of the sample.
[0019] Figure 3 The CoMn prepared in Example 1 of the present invention 2 O 4 TEM image of the sample.
[0020] Figure 4 It is a schematic structural diagram of the subcritical hydrothermal reaction device of the present invention. DETAILED DESCRIPTION
[0021] The present invention will be further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0022] The mass concentration of ammonia water in the embodiment of the present invention is 25-28%.
[0023] The structural schematic diagram of the subcritical hydrothermal reaction device used in the embodiment of the present invention is as follows Figure 4 As shown, it includes a reactor 5 and a constant temperature heating jacket 6 arranged outside the reactor 5 for heating the reactor 5. A stirring magnet is added inside the reactor 5, and the reactor 5 is placed on a magnetic stirrer. An air inlet 7 and an air outlet 8 are arranged on the top of the reactor 5. The air inlet 7 is connected to the nitrogen bottle 1 through a pipeline via an air inlet valve 4, a flow meter 3, and a gas delivery pump 2. The air outlet 8 is connected to an exhaust pipe with an exhaust valve 13. A temperature measuring port 9 is also arranged on the top of the reactor 5. A temperature measuring probe 11 extends into the reactor 5 through the temperature measuring port 9 to detect the liquid temperature inside the reactor 5. A pressure detection port 10 is arranged on the top of the reactor 5, and the pressure detection port is connected to a pressure sensor 12.
[0024] Example 1 Preparation of CoMn by subcritical temperature and pressure control 2 O 4 Catalyst, the steps are as follows: 1) 1.5 mmol Co(NO 3 ) 2 6H 2 O was dissolved in 30 mL ultrapure water and dispersed evenly by ultrasonication. Then 3 mmol Mn(NO 3 ) 2 ·4H 2O was dissolved in 30 mL ultrapure water and dispersed evenly by ultrasonication. The two solutions were mixed and continuously stirred by magnetic stirring. Ammonia water was dropped into the mixture to adjust the pH to 11 and stirred to mix evenly.
[0025] 2) The mixed solution obtained in step 1) is transferred into a temperature- and pressure-controlled reactor, the reactor is sealed, and nitrogen is introduced to remove air and oxygen in the system while maintaining magnetic stirring. While heating the reactor, pressurized N is introduced into the reactor. 2 The temperature in the reactor was precisely controlled to be 180°C and the gas pressure in the reactor was 1.5 MPa. The reaction lasted for 180 min and then centrifuged. The solid obtained by centrifugation was washed three times with water and anhydrous ethanol respectively. The washed material was placed in a vacuum drying oven and vacuum dried at 80°C for 12 h. The dried solid was calcined at 350°C in a muffle furnace to obtain the CoMn 2 O 4 catalyst.
[0026] CoMn prepared in Example 1 2 O 4 The characterization results of XRD, SEM and TEM images of the catalyst are shown in Figure 1 , Figure 2 and Figure 3 , XRD results show that CoMn 2 O 4 The SEM and TEM images show that the CoMn prepared by the method of the present invention 2 O 4 It has a granular nanostructure and abundant active sites.
[0027] Example 2 Preparation of CuMn by Subcritical Technology Temperature and Pressure Control 2 O 4 catalyst Example 2 CuMn 2 O 4 The preparation method of the catalyst was repeated in Example 1, except that "Co(NO 3 ) 2 6H 2 O was replaced by an equal molar amount of Cu(NO 3 ) 2 2.5H 2 O", the other conditions remain unchanged, and finally the CuMn 2 O 4 catalyst.
[0028] Example 3 Preparation of NiMn by Subcritical Technology Temperature and Pressure Control 2 O 4 catalyst Example 3 NiMn2 O 4 The preparation method of the catalyst was repeated in Example 1, except that "Co(NO 3 ) 2 6H 2 O was replaced by an equal molar amount of Ni(NO 3 ) 2 6H 2 O", the other conditions remain unchanged, and finally the NiMn 2 O 4 catalyst.
[0029] Example 4 Preparation of MgMn by Subcritical Technology Temperature and Pressure Control 2 O 4 catalyst Example 4 MgMn 2 O 4 The preparation method of the catalyst was repeated in Example 1, except that "Co(NO 3 ) 2 6H 2 O is replaced by an equal molar amount of Mg(NO 3 ) 2 6H 2 O", the other conditions remain unchanged, and finally the MgMn 2 O 4 catalyst.
[0030] Example 5 Preparation of FeMn by Subcritical Technology Temperature and Pressure Control 2 O 4 catalyst Example 5 FeMn 2 O 4 The preparation method of the catalyst was repeated in Example 1, except that "Co(NO 3 ) 2 6H 2 O is replaced by an equal molar amount of Fe(NO 3 ) 2 9H 2 O", the other conditions remain unchanged, and finally the FeMn 2 O 4 catalyst.
[0031] Example 6 Preparation of ZnMn by Subcritical Technology Temperature and Pressure Control 2 O 4 catalyst Example 6 ZnMn 2 O 4 The catalyst preparation method was repeated in Example 1, except that "Co(NO 3 ) 2 6H2 O is replaced by an equal molar amount of Zn(NO 3 ) 2 6H 2 O", the other conditions remain unchanged, and finally the ZnMn 2 O 4 catalyst.
[0032] Example 7 Preparation of MnAl by Subcritical Technology Temperature and Pressure Control 2 O 4 catalyst 1) 1.5 mmol Mn(NO 3 ) 2 ·4H 2 O was dissolved in 30 mL ultrapure water and dispersed evenly by ultrasonication. Then 3 mmol Al(NO 3 ) 2 9H 2 O was dissolved in 30 mL ultrapure water and dispersed evenly by ultrasonication. The two solutions were mixed and magnetic stirring was continued. Ammonia water was dropped into the mixture to adjust the pH to 11 and the mixture was stirred and mixed evenly.
[0033] 2) The mixed solution obtained in step 1) is transferred into a temperature- and pressure-controlled reactor, the reactor is sealed, and nitrogen is introduced to remove air and oxygen in the system while maintaining magnetic stirring. While heating the reactor, pressurized N is introduced into the reactor. 2 The temperature in the reactor is precisely controlled to be 180°C and the gas pressure in the reactor is 1.5 MPa. The reaction lasts for 180 min and then centrifuged. The solid obtained by centrifugation is washed three times with water and anhydrous ethanol respectively. The washed material is placed in a vacuum drying oven and vacuum dried at 80°C for 12 h. The dried solid is calcined at 350°C in a muffle furnace to obtain the MnAl 2 O 4 catalyst.
[0034] Example 8 Preparation of MnGa by Subcritical Technology Temperature and Pressure Control 2 O 4 catalyst Example 8 MnGa 2 O 4 The steps for preparing the catalyst were repeated in Example 7, except that "Al(NO 3 ) 2 9H 2 O is replaced by an equal molar amount of Ga(NO 3 ) 2 9H 2 O", the other conditions remain unchanged, and finally the MnGa 2 O 4 catalyst.
[0035] Example 9 Preparation of MnIn by Subcritical Technology Temperature and Pressure Control 2 O 4 catalyst Example 9 MnIn 2 O 4 The steps for preparing the catalyst were repeated in Example 8, except that "Ga(NO 3 ) 2 9H 2 O is replaced by an equal molar amount of In(NO 3 ) 2 6H 2 O", the other conditions remain unchanged, and finally the MnIn 2 O 4 catalyst.
[0036] Example 10 Preparation of FeCo by subcritical temperature and pressure control 2 O 4 Catalyst and application, steps are as follows: 1) Add 1.5 mmol Fe(NO 3 ) 2 9H 2 O was dissolved in 30 mL ultrapure water and dispersed evenly by ultrasonication. Then 3 mmol Co(NO 3 ) 2 6H 2 O was dissolved in 30 mL ultrapure water and dispersed evenly by ultrasonication. The two solutions were mixed and magnetic stirring was continued. Ammonia water was dropped into the mixture to adjust the pH to 11 and the mixture was stirred and mixed evenly.
[0037] 2) The mixed solution obtained in step 1) is transferred into a temperature- and pressure-controlled reactor, the reactor is sealed, and nitrogen is introduced to remove air and oxygen in the system while maintaining magnetic stirring. While heating the reactor, pressurized N is introduced into the reactor. 2 The temperature in the reactor was precisely controlled to be 180°C and the gas pressure in the reactor was 1.5 MPa. The reaction lasted for 180 min and then centrifuged. The solid obtained by centrifugation was washed three times with water and anhydrous ethanol respectively. The washed material was placed in a vacuum drying oven and vacuum dried at 80°C for 12 h. The dried solid was calcined at 350°C in a muffle furnace to obtain the FeCo 2 O 4 catalyst.
[0038] Example 11 Preparation of ZnCo by subcritical temperature and pressure control 2 O 4 catalyst Example 11 ZnCo 2 O4 The steps for preparing the catalyst were repeated in Example 10, except that "Fe(NO 3 ) 2 9H 2 O is replaced by an equal molar amount of Zn(NO 3 ) 2 6H 2 O", the other conditions remain unchanged, and finally the ZnCo 2 O 4 catalyst.
[0039] Example 12 Preparation of CuCo by subcritical temperature and pressure control 2 O 4 catalyst Example 12 CuCo 2 O 4 The steps for preparing the catalyst were repeated in Example 10, except that "Fe(NO 3 ) 2 9H 2 O was replaced by an equal molar amount of Cu(NO 3 ) 2 2.5H 2 O", the other conditions remain unchanged, and finally the CuCo 2 O 4 catalyst.
[0040] Example 13 Preparation of Cu by subcritical temperature and pressure control 0.7 Zn 0.3 Co 2 O 4 Catalyst and application, steps are as follows: 1) 1.05 mmol Cu (NO 3 ) 2 2.5H 2 O and 0.45 mmol Zn (NO 3 ) 2 6H 2 O was dissolved in 30 mL ultrapure water and dispersed evenly by ultrasonication. Then 3 mmol Co(NO 3 ) 2 6H 2 O was dissolved in 30 mL ultrapure water and dispersed evenly by ultrasonication. The two solutions were mixed and magnetic stirring was continued. Ammonia water was dropped into the mixture to adjust the pH to 11 and the mixture was stirred and mixed evenly.
[0041] 2) The mixed solution obtained in step 1) is transferred into a temperature- and pressure-controlled reactor, the reactor is sealed, and nitrogen is introduced to remove air and oxygen in the system while maintaining magnetic stirring. While heating the reactor, pressurized N is introduced into the reactor.2 The temperature in the reactor was precisely controlled to be 180°C and the gas pressure in the reactor was 1.5 MPa. The reaction lasted for 180 min and then centrifuged. The solid obtained by centrifugation was washed three times with water and anhydrous ethanol respectively. The washed material was placed in a vacuum drying oven and vacuum dried at 80°C for 12 h. The dried solid was calcined at 350°C in a muffle furnace to obtain the Cu 0.7 Zn 0.3 Co 2 O 4 catalyst.
[0042] The catalysts prepared in Examples 1-13 were characterized by SEM, showing that the catalysts prepared by the method of the present invention all had a granular nanostructure.
[0043] Example 14 Preparation of CoMn by Subcritical Technology Temperature Control 2 O 4 catalyst: 1) 1.5 mmol Co(NO 3 ) 2 6H 2 O was dissolved in 30 mL ultrapure water and dispersed evenly by ultrasonication. Then 3 mmol Mn(NO 3 ) 2 ·4H 2 O was dissolved in 30 mL ultrapure water, dispersed evenly by ultrasonication, and the two solutions were mixed with continuous magnetic stirring. Ammonia water was added dropwise to the mixture to adjust the pH to 11, and the mixture was stirred and mixed evenly.
[0044] 2) Transfer the mixed solution obtained in step 1) into a temperature- and pressure-controlled reactor, seal the reactor, and introduce nitrogen to remove air and oxygen from the system while maintaining magnetic stirring. Heat the reactor and stop introducing pressurized N into the reactor. 2 The temperature in the reactor was controlled to be 200 °C by a heating device. When the temperature of the reactor reached 200 °C, the autogenous pressure in the reactor reached 1.5 MPa. The reaction lasted for 180 min and then centrifuged. The solid obtained by centrifugation was washed three times with water and anhydrous ethanol respectively. The washed material was placed in a vacuum drying oven and vacuum dried at 80 °C for 12 h. The dried solid was calcined at 350 °C in a muffle furnace to obtain the CoMn 2 O 4 catalyst.
[0045] Example 15 Preparation of CoMn by Subcritical Technology Temperature and Pressure Control 2 O 4 Catalyst and application, steps are as follows: 1.5 mmol Co(NO 3 )2 6H 2 O was dissolved in 30 mL ultrapure water and dispersed evenly by ultrasonication. Then 3 mmolMn(NO 3 ) 2 ·4H 2 O was dissolved in 30 mL of ultrapure water, ultrasonically dispersed evenly, the two solutions were mixed, and continuous magnetic stirring was performed. Ammonia water was dropped into the mixed solution, the pH was adjusted to 11, and after stirring and mixing evenly, it was transferred to the reactor. The reactor was sealed, and nitrogen was introduced to remove air and oxygen in the system, while magnetic stirring was maintained. While heating the reactor, pressurized N was introduced into the reactor. 2 The temperature in the reactor was precisely controlled to be 150°C and the gas pressure in the reactor was 1.5 MPa. The reaction lasted for 180 min and then centrifuged. The solid obtained by centrifugation was washed three times with water and anhydrous ethanol respectively. The washed material was placed in a vacuum drying oven and vacuum dried at 80°C for 12 h. The dried solid was calcined at 350°C in a muffle furnace to obtain the CoMn 2 O 4 catalyst.
[0046] Application Example 1 The catalyst is used for the oxidation reaction of 5-hydroxymethylfurfural, and the specific process is as follows: A microreactor device was used, the inner tank was 25 mL, and the heating jacket was used to heat and control the temperature. 50 mg of catalyst, 0.042 g of sodium bicarbonate, and 5 mL of 50 mM 5-hydroxymethylfurfural aqueous solution were added to the inner tank of the microreactor device. The microreactor device was sealed, magnetic stirring was continued at 600 rpm, oxygen was pressurized to 1.5 MPa, the reaction temperature was set to 130 ° C, and the temperature was raised from room temperature at a heating rate of 2 ° C / min. After the temperature reached 130 ° C, the reaction time at 130 ° C was started, and the reaction liquid with a reaction time of 8 hours was taken for analysis and detection, and the conversion rate and yield of 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid were calculated.
[0047] According to the above experimental process, when the catalysts prepared in Examples 1-15 are used respectively, the conversion rates and yields of 5-hydroxymethylfurfural converted to 2,5-furandicarboxylic acid by the catalysts of different Examples are shown in Table 1.
[0048] Table 1 .
[0049] From Table 1 we can see that: 1) The composition of the catalyst has a great influence on the catalytic activity of the 5-hydroxymethylfurfural oxidation reaction. Non-precious metal Mn, Co, and Cu-based multi-metal oxide materials have excellent catalytic effects. In addition, CuCo 2 O4 Adding a small amount of Zn into the catalyst can also achieve good catalytic reaction effects.
[0050] 2) Comparing the catalytic reaction results of Example 1 with those of Examples 14 and 15, it can be seen that when the gas pressure in the reactor during catalyst preparation is also 1.5 MPa, different reaction temperatures have a relatively large impact on the catalyst activity.
[0051] In order to test the performance of the prepared catalyst, the CoMn prepared in Example 1 was subjected to oxidation of 5-hydroxymethylfurfural. 2 O 4 The catalyst was repeatedly applied and investigated. After each batch of reaction was completed for 8 hours, the catalyst was centrifuged and then washed with deionized water before being put into the next batch of 5-hydroxymethylfurfural oxidation reaction. 2 O 4 After the catalyst underwent five 5-hydroxymethylfurfural oxidation cycle experiments, the yield of FDCA fluctuated only slightly, with a fluctuation range of about 1.5%. This shows that the catalyst prepared by the present invention has excellent stability, can be repeatedly used, and has industrial prospects.
[0052] Comparative Example 1: Preparation of Mn by conventional hydrothermal method 3 O 4 Catalyst and application, steps are as follows: 2.25 mmol Mn(NO 3 ) 2 ·4H 2 O was dissolved in 30 mL ultrapure water, ultrasonically dispersed to obtain a mixed solution, and magnetic stirring was continued. Ammonia water was added to adjust the pH to 11. After stirring and mixing, the mixture was transferred into a 50 mL polytetrafluoroethylene liner of a reactor. The stainless steel reactor was sealed and reacted at 180 ° C for 8 h and then centrifuged. The obtained solid was washed with water and anhydrous ethanol for 3 times, and the washed material was placed in a vacuum drying oven and vacuum dried at 80 ° C for 12 h to obtain the Mn 3 O 4 catalyst.
[0053] Mn prepared in Comparative Example 1 3 O 4 The SEM image of the catalyst shows that the prepared Mn 3 O 4 It has a nanosphere cluster structure.
[0054] Using the catalytic method of Example 1, Mn prepared in Comparative Example 1 3 O 4The sample was used for 5-hydroxymethylfurfural oxidation reaction. Under the conditions of reaction temperature of 130 ℃ and reaction time of 8 h, the 5-hydroxymethylfurfural conversion rate could reach 100% after the 5-hydroxymethylfurfural oxidation reaction reached stability, and the maximum yield of 2,5-furandicarboxylic acid was 26.7%.
[0055] Comparative Example 2 Preparation of Co by Traditional Hydrothermal Method 3 O 4 Catalyst and application, steps are as follows: 2.25 mmol Co(NO 3 ) 2 6H 2 O was dissolved in 30 mL ultrapure water, ultrasonically dispersed to obtain a mixed solution, and magnetic stirring was continued. Ammonia water was added to adjust the pH to 11. After stirring and mixing, the mixture was transferred into a 50 mL polytetrafluoroethylene liner of a reactor. The stainless steel reactor was sealed and reacted at 180 ° C for 8 h and then centrifuged. The obtained solid was washed with water and anhydrous ethanol for 3 times, and the washed material was placed in a vacuum drying oven and vacuum dried at 80 ° C for 12 h to obtain the Co 3 O 4 catalyst.
[0056] Co prepared in Comparative Example 2 3 O 4 The SEM image of the catalyst shows that the prepared Co 3 O 4 It has a nanosphere cluster structure.
[0057] Using the catalytic method of Example 1, Co prepared in Comparative Example 2 3 O 4 The sample was used for 5-hydroxymethylfurfural oxidation reaction. Under the conditions of reaction temperature of 130 ℃ and reaction time of 8 h, the 5-hydroxymethylfurfural conversion rate after the 5-hydroxymethylfurfural oxidation reaction reached stability could reach 89.7%, and the 2,5-furandicarboxylic acid conversion rate could reach up to 18.9%.
[0058] Comparative Example 3: Preparation of Fe by conventional hydrothermal method 3 O 4 Catalyst and application, steps are as follows: Add 2.25 mmol Fe(NO 3 ) 2 9H 2O was dissolved in 30 mL ultrapure water, ultrasonically dispersed to obtain a mixed solution, and magnetic stirring was continued. Ammonia water was added to adjust the pH to 11. After stirring and mixing, the mixture was transferred into a 50 mL polytetrafluoroethylene liner of a reactor. The stainless steel reactor was sealed and reacted at 180 ° C for 8 h and then centrifuged. The obtained solid was washed with water and anhydrous ethanol for 3 times, and the washed material was placed in a vacuum drying oven and vacuum dried at 80 ° C for 12 h to obtain the Fe 3 O 4 catalyst.
[0059] Using the catalytic method of Example 1, Fe 3 O 4 The sample was used for 5-hydroxymethylfurfural oxidation reaction. Under the conditions of reaction temperature of 130 ℃ and reaction time of 8 h, the 5-hydroxymethylfurfural conversion rate after the 5-hydroxymethylfurfural oxidation reaction reached stability could reach 76.9%, and the maximum yield of 2,5-furandicarboxylic acid was 11.7%.
[0060] Comparative Example 4 Preparation of CoMn by Subcritical Technology Temperature Control 2 O 4 Catalyst and application, steps are as follows: 1.5 mmol Co(NO 3 ) 2 6H 2 O was dissolved in 30 mL ultrapure water and dispersed evenly by ultrasonication. Then 3 mmolMn(NO 3 ) 2 ·4H 2 O was dissolved in 30 mL of ultrapure water, ultrasonically dispersed evenly, the two solutions were mixed, and continuous magnetic stirring was performed. Ammonia water was dropped into the mixed solution, the pH was adjusted to 11, and after stirring and mixing evenly, it was transferred into the reactor. The reactor was sealed and magnetic stirring was maintained. The temperature in the reactor was controlled to 150 °C by a heating device. When the temperature of the reactor reached 150 °C, the autogenous pressure of the water in the reactor was 0.4 MPa. The reaction lasted for 180 min and then centrifuged. The solid obtained by centrifugation was washed 3 times with water and anhydrous ethanol respectively. The washed material was placed in a vacuum drying oven and vacuum dried at 80 °C for 12 h. The dried solid was calcined at 350 °C in a muffle furnace to obtain the CoMn 2 O 4 catalyst.
[0061] CoMn prepared in Comparative Example 4 2 O 4 The sample was used for the oxidation reaction of 5-hydroxymethylfurfural, and the basic steps were the same as those of the catalyst used in Example 1-15 for the oxidation reaction of 5-hydroxymethylfurfural, except that the catalyst was CoMn prepared in Comparative Example 4. 2 O4 Under the conditions of reaction temperature of 130 ℃ and reaction time of 8 h, the 5-hydroxymethylfurfural conversion rate can reach 100% after the 5-hydroxymethylfurfural oxidation reaction reaches stability, and the yield of 2,5-furandicarboxylic acid is as high as 68.7%.
[0062] Comparative Example 5 Preparation of CoMn by Subcritical Technology Temperature Control 2 O 4 Catalyst and application, steps are as follows: 1.5 mmol Co(NO 3 ) 2 6H 2 O was dissolved in 30 mL ultrapure water and dispersed evenly by ultrasonication. Then 3 mmolMn(NO 3 ) 2 ·4H 2 O was dissolved in 30 mL of ultrapure water, ultrasonically dispersed evenly, the two solutions were mixed, and continuous magnetic stirring was performed. Ammonia water was dropped into the mixed solution, the pH was adjusted to 11, and after stirring and mixing evenly, it was transferred into the reactor. The reactor was sealed and magnetic stirring was maintained. The temperature in the reactor was controlled to 180 °C by a heating device. When the temperature of the reactor reached 180 °C, the autogenous pressure of the water in the reactor was 0.93 MPa. The reaction lasted for 180 min and then centrifuged. The solid obtained by centrifugation was washed 3 times with water and anhydrous ethanol respectively. The washed material was placed in a vacuum drying oven and vacuum dried at 80 °C for 12 h. The dried solid was calcined at 350 °C in a muffle furnace to obtain the CoMn 2 O 4 catalyst.
[0063] CoMn prepared in Comparative Example 5 2 O 4 The sample was used for the oxidation reaction of 5-hydroxymethylfurfural, and the basic steps were the same as those of the catalyst used in Example 1-13 for the oxidation reaction of 5-hydroxymethylfurfural, except that the catalyst was CoMn prepared in Comparative Example 5. 2 O 4 Under the conditions of reaction temperature of 130 ℃ and reaction time of 8 h, the 5-hydroxymethylfurfural conversion rate can reach 100% after the 5-hydroxymethylfurfural oxidation reaction reaches stability, and the yield of 2,5-furandicarboxylic acid is as high as 83.7%.
[0064] The conclusions of the comparison between the embodiments and the comparative examples are as follows: 1) By comparing the experimental results of Comparative Examples 1-3 with Comparative Examples 4-5, it can be seen that in the reaction of HMF oxidation to FDCA, the multi-metal catalyst has abundant active sites due to the synergistic effect of multiple metals, and exhibits characteristics superior to those of a single metal oxide.
[0065] 2) From the comparison of Comparative Examples 4 and 5, it can be seen that in the reaction of HMF oxidation to FDCA, CoMn 2 O 4 , CoMn prepared at 180 ℃ 2 O 4 It has better catalytic activity.
[0066] 3) From the comparison between Example 1 and Comparative Example 5, it can be seen that in the reaction of HMF oxidation to FDCA, the catalyst prepared by controlled pressure under subcritical state has better catalytic activity than the catalyst prepared by conventional autogenous pressure. This is attributed to the fact that under relatively high pressure environment, the changes in the reaction rate and pressure of the system lead to differences in the active sites of the surface structure of the nanomaterial, which directly affects the activity performance of the material.
[0067] The contents described in this specification are merely an enumeration of implementation forms of the inventive concept, and the protection scope of the present invention should not be regarded as being limited to the specific forms described in the embodiments.
Claims
1. A method for preparing nanostructured multi-metal oxides, characterized in that The following steps are involved: Step 1: dissolving a metal salt in an aqueous solvent, uniformly dispersing the mixture by ultrasonication, dripping an alkaline additive solution into the mixture under stirring, and fully stirring and mixing the mixture to obtain a uniform mixed solution; wherein the metal salt is a chloride, nitrate, acetate or sulfate corresponding to two or more metal elements selected from magnesium, aluminum, iron, cobalt, manganese, nickel, copper, zinc, gallium and indium; Step 2: The mixed solution obtained in step 1 is transferred into a temperature- and pressure-controlled reactor, and the temperature and pressure of the reactor are adjusted to make the liquid in the reactor reach a subcritical state, and react to rapidly form nanoparticles; Step 3: centrifugally separating the mixed suspension prepared in step 2, and sequentially washing, drying, and grinding to obtain a multi-metal oxide precursor; Step 4: placing the multi-metal oxide precursor prepared in step 3 in a muffle furnace for calcining to obtain the multi-metal oxide; The reaction temperature of step 2 is 150-200°C, and the reaction pressure is 0.4-5 MPa.
2. The method for preparing a nanostructured multi-metal oxide according to claim 1, characterized in that The metal salt in step 1 is a salt of two metals, the first metal is Mn, the second metal is Co, Cu or Ni, and the molar ratio of the first metal to the second metal is 1.5-3:1, preferably 2-2.5:
1.
3. The method for preparing a nanostructured multi-metal oxide according to claim 1, characterized in that The metal salt in step 1 is a salt of two metals, the first metal is Co, the second metal is Cu or Cu and Zn, the molar ratio of the first metal to the second metal is 1.5-3:1, preferably 2-2.5:1; when the second metal is Cu and Zn, the molar ratio of the two is 1.5-3:1, preferably 2-2.5:
1.
4. The method for preparing a nanostructured multi-metal oxide according to claim 1, characterized in that In step 1, the alkaline additive solution is an aqueous solution of at least one of sodium hydroxide, potassium hydroxide, ammonia water, sodium carbonate and potassium carbonate, and the alkaline additive solution is dripped into the metal salt solution to adjust the pH to 9-12.
5. The method for preparing a nanostructured multi-metal oxide according to claim 1, characterized in that In step 2, the reaction temperature is 170-180°C. By introducing pressurized nitrogen into the reactor, the reaction pressure in the reactor is made higher than the autogenous pressure of water in the reactor, and the reaction pressure is adjusted to 1.5-2 MPa.
6. The method for preparing a nanostructured multi-metal oxide according to claim 1, characterized in that The calcination temperature in step 4 is 300-400°C.
7. A nanostructured multi-metal oxide prepared by the method according to any one of claims 1 to 6.
8. Use of the nanostructured multi-metal oxide as claimed in claim 7 in catalyzing the oxidation reaction of 5-hydroxymethylfurfural to prepare 2,5-furandicarboxylic acid.
9. The use according to claim 8, characterized in that The multi-metal oxide, alkaline additive and 5-hydroxymethylfurfural solution are added to a microreactor with controllable temperature and pressure, and the microreactor is sealed to catalyze the oxidation of 5-hydroxymethylfurfural to generate 2,5-furandicarboxylic acid under the conditions of temperature of 100-150°C, oxygen pressure of 0.5-4 MPa and continuous magnetic stirring; after the reaction is completed, the multi-metal oxide material is centrifuged and recovered.
10. The use according to claim 9, characterized in that The concentration of the 5-hydroxymethylfurfural solution is 10-100 mM, and the mass ratio of the multi-metal oxide to 5-hydroxymethylfurfural is 1.2-2:1; the alkaline additive is sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate or calcium hydroxide, and the molar ratio of the alkaline additive to 5-hydroxymethylfurfural is 1~4:1.
Citation Information
Patent Citations
Magnetic nano ozone catalyst CoFe2O4 as well as preparation method and application thereof
CN109364924A
Preparation method of copper-chromium-aluminum hydrotalcite catalyst and application of catalyst in catalytic oxidation of 5-hydroxymethylfurfural
CN110586114A
Catalyst for preparing 1,2-dimethylimidazole and preparation method thereof
CN113171770A
Modified composite catalyst, preparation method thereof and application of modified composite catalyst in catalyzing thermal oxidative decomposition of toluene
CN114082422A
Method for preparing sugar by catalyzing hydrogenation degradation of straws through non-noble metal
CN115197283A
Cited By
Copper-based catalyst as well as preparation method and application thereof
CN122298407A